Boycott as Symbolic Action: An Analysis of Social Action in Support of Palestine - Hasuna, Asma Nadia; Nurkhurairokh, Azzahra; Fauziah, Rafa Annisa; Ayu, Salwa Laila; Hufad, Achmad; Achdiani, Yani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The feud between Palestine and Israel has lasted more than seven decades, causing deep suffering for the Palestinian people who experience refugee camps, restrictions on human rights, and lack of basic needs. In this context, a boycott of products affiliated with Israel emerged as a form of moral and political protest, reflecting global solidarity and social values that underlie individual and collective participation in the movement. This study aims to study the boycott of products affiliated with Israel as symbolic social actions, and identify the types of underlying social actions, including rational actions, rational instrumental, affective, and traditional. In addition, this research also understands the motivation and meaning behind individual and collective participation in the boycott movement, using the theoretical framework of Max Weber's social action. This study uses secondary and primary data. Secondary data obtained from articles, journals, and relevant internet sources. Primary data is collected through questionnaires to obtain information directly from respondents. The combination of these two types of data allows an understanding of respondents' perceptions and experiences related to a boycott of products that support Israel, with voluntary and anonymous participation. This study found that the boycott actions reflect the types of social action Max Weber, driven by sympathy and human values, and were influenced by social media and support of public figures. Respondents interpret the boycott as an act of economic impact and moral statement of injustice, a social action that reflects values, emotions, and rationality in solidarity with Palestine.